2010
DOI: 10.1179/037366810x12578498136075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analyses of haploid and allopolyploidPelliaspecies

Abstract: The allopolyploid origin of several bryophyte species was reported approximately 20 years ago. Among them the best characterized is Pellia borealis, a hybrid of two cryptic sibling species: Pellia epiphylla-species N and P. epiphylla-species S. Genomes of the allopolyploid liverwort P. borealis and its progenitors were investigated using conventional as well as molecular cytogenetic techniques. The nuclear DNA content and cell cycle phase in the thallus nuclei was established using flow cytometry. Fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…In pteridophytes, the rDNA sites have been observed only in four genera ( Osmunda , Ceratopteris , Acrostichum [10] and Selaginella [11]), all of them with terminal or subterminal sites. In bryophytes, data were found only for Marchantia polymorpha [12] and species of Pellia [13], all of them with rDNA sites in terminal position. In a recent paper, a rDNA database containing crude data from a similar sample of plant species has been developed allowing easy access to a large amount of data [14].…”
Section: Introductionmentioning
confidence: 99%
“…In pteridophytes, the rDNA sites have been observed only in four genera ( Osmunda , Ceratopteris , Acrostichum [10] and Selaginella [11]), all of them with terminal or subterminal sites. In bryophytes, data were found only for Marchantia polymorpha [12] and species of Pellia [13], all of them with rDNA sites in terminal position. In a recent paper, a rDNA database containing crude data from a similar sample of plant species has been developed allowing easy access to a large amount of data [14].…”
Section: Introductionmentioning
confidence: 99%
“…In bryophytes, cryptic speciation has been increasingly reported (e.g., Heinrichs et al, 2010;Kreier et al, 2010;Orzechowska et al, 2010;Ramaiya et al, 2010) and might offer an explanation for one of the most striking biogeographic features of bryophytes, that is, the extremely low rates of endemism of their floras (see Vanderpoorten et al, 2010a for review). In Macaronesia for example, a biogeographic region comprised of the mid-Atlantic archipelagos of the Azores, Madeira, and the Canary Islands, and which is recognized as an important floristic area for conservation within the European-Mediterranean climate region (Médail and Quezel, 1997), less than 2% of species are endemic to the Canarian archipelago, strongly paling in comparison with the 40% endemism rates observed in angiosperms (Vanderpoorten et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of 5S rDNA sites was also considered with regard to 45S rDNA sites, aiming to evaluate if the chromosomal linkage of these sites depends only on their abundance in the karyotypes. For bryophytes, information about 5S rDNA was found only for some species of Marchantia and Pellia [Fujisawa et al, 2003;Orzechowska et al, 2010], and for pterydophytes no data were found in the literature. Therefore, these groups were not included in this analysis.…”
mentioning
confidence: 99%